ANALISIS PERMOHONAN KREDIT DALAM UPAYA MENCEGAH KREDIT MACET DI PERUSAHAAN MANUFAKTUR - Riffka Fauzany; Vellysha Tyvanov; Hadistin Syafel; Citra Meilani; Akbar Meiludin; Gunardi Gunardi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to analyze credit applications in an effort to prevent bad debts in manufacturing companies and identify effective strategies to overcome these credit risks. Qualitative research is the methodology employed. Qualitative research is descriptive analysis that collects data in-depth with the goal of describing phenomena as deeply as possible. Because this research focuses on the real issue, it does not necessitate the formation of several hypotheses. Literature, records, journals, and reports are the sources of this data collection.The results of this study show that careful analysis of credit applications is instrumental in minimizing the risk of bad debts. Factors such as the use of artificial intelligence-based technology, improved human resource competencies, and the implementation of a risk assessment system have been proven to reduce the potential for default. In addition, a thorough evaluation of the prospective borrower's profile and regular supervision contribute significantly to the effectiveness of credit management in manufacturing companies.